Further Development of the Food Industry - Kurbonov Dilbarjon; Мirzaaxmatova Zubayda (Zien Journals, 2022)
This article discusses the further enhancement of the republic's potential in the field of processing agricultural products, the development of production, processing, standardization, consulting and marketing services on agribusiness issues, fully consistent with the ongoing reforms and the requirements of the time, the introduction of modern technologies in the agricultural sector
Keywords: Processing; agricultural products; consulting; marketing